A classification of the Veldkamp lines of the near hexagon Lsub3timesGQ(2, 2) - Green, R. M. (Ars mathematica contemporanea, 2017)
Using a standard technique sometimes (inaccurately) known as Burnside's Lemma, it is shown that the Veldkamp space of the near hexagon ?$L_3 × \text{GQ}(2, 2)$? features 156 different types of lines. We also give an explicit description of each type of a line by listing the types of the three geometric hyperplanes it consists of and describing the properties of its core set, that is the subset of points of ?$L_3 × \text{GQ}(2, 2)$? shared by the three geometric hyperplanes in question.
Keywords: bližnji heksagoni; geometrijske hiperravnine; Veldkampovi prostori